Merchandising televisivo: a força dos testemunhais de produtos em programas femininos - Paula, Amadeu Nogueira de (2018)
This study presents an analysis of the general elements in the subtle or non-subtle testemonials represented by individuals hired by advertisers for the promotion of their brands in the mass media, specifically television. The historical definition of product placement had, at first, the clarification that the advertising message should be carried out subtly, incorporating itself in the content so that consumers did not perceive it; because if this perception happened, the tendency would be to reject the advertisement. This argument remained for some time, however a significant variable emerged in the context of women’s television programs, in which the brand presenter dialogues in a non-subtle way, endorsing the consumer experience, strengthening the narrative with lived stories of sucessful experiences. It is the materialization of the product in people’s lives, through entertainment and information, which is a reference for the viewers present in the audience of the program. The main objective of this research was to analyze the use of brands’ testemonials advertisement as a communication tool in women’s programs of open television presented in a non-subtle way by brand communicators, called merchandetes. Thus, the research focused on the analysis of the product placement – better known in Brazil as merchandising – in the television program Mulheres, from TV Gazeta, in São Paulo, setting up a case study in a women’s program broadcast in the afternoon. In addition, it was interviewed managers advertisers of frequent testemonials announcements, merchandetes of others women’s programs and a commnunication manager in social network. The investigation showed the importance and commercial strength of merchandising not only as part of the content of women’s programs, but also in relation to the others formats of advertising. The study emphasizes the importance of the endorsement carried out, either by the merchandete or the program’s TV host, as a fundamental tool to generate the immediate sales of the announced products in real time. The originality of this study consists in the understanding of the permanence in the context of the testimonial merchandising as an effective advertising format in Brazilian television from its origin, where the placement of products was made exclusively through the so-called “brand’s speakers”, who existed because of the transmissions performed exclusively live. The interviews revealed that all the participants in the commercial and artistic structure of the broadcaster that generates the women’s program seek to monetize the arguments and quality of the messages in order to effectively achieve the goals of their advertisers when the ads are broadcasted. This study also demonstrates technically, through audience data, investments and number of insertions, the intense presence of the testemonials advertisers broadcasting in the daytime, where are the greater participation of the investments and concentration of viewers conformed by the audience surveys predominate.